The associations between EFL learners' L2 class belongingness, emotion regulation strategies, and perceived L2 proficiency in an online learning context - Yuksel, H. Gulru; Solhi, Mehdi; Ozcan, Emrah; Giritlioglu, Necla Burcin (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2025)
Although the sense of belongingness plays a major influence in fostering intrinsic motivation and psychological well-being, scant research attention has been given to English as a foreign language (EFL) learners' belongingness in relation to peers and teachers and its outcomes in L2 learning contexts. Additionally, despite the importance of emotion regulation in L2 education, little is known about its role in mediating the impact of L2 belongingness on self-assessment of L2 proficiency in online L2 learning environments. Therefore, the present study used survey data to examine the associations between learners' sense of class belongingness, their preferred emotional regulation strategies (reappraisal vs. suppression) and self-perceived English proficiency, in a sample of 191 Turkish EFL university students. Path analysis results indicated significant direct paths between social belongingness with peers and academic belongingness with teachers, respectively, and the emotional regulation strategy of reappraisal. Further analysis indicated a significant indirect association between social belongingness with peers and perceived L2 proficiency through the measure of reappraisal emotional regulation. There was also a significant indirect relationship via reappraisal between academic belongingness with teachers and perceived L2 proficiency. The results are discussed in connection with self-determination theory and social identity theory, and implications are drawn for teaching.
Keywords: L2 academic belongingness; social belongingness; emotion regulation strategies; perceived English proficiency; SOCIAL SUPPORT; EXPRESSIVE SUPPRESSION; HIGH-SCHOOL; ENGAGEMENT; AUTONOMY; STUDENTS; SENSE; WILLINGNESS; RELATEDNESS; COMMUNICATE; Education & Educational Research